Genetic variability of two Italian indigenous chicken breeds inferred from microsatellite marker analysis. Issue 4 (3rd July 2016) - Sartore, S.; Sacchi, P.; Soglia, D.; Maione, S.; Schiavone, A.; De Marco, M.; Ceccobelli, S.; Lasagna, E.; Rasero, R.
Abstract: The objective of this study was to determine the genetic structure and variability of Bionda Piemontese and Bianca di Saluzzo (Piedmont, Northwest Italy) using an international set of microsatellite loci (AVIANDIV-FAO). Differences compared with commercial lines and other Italian breeds were verified to justify the implementation of conservation programmes. Flock contribution to genetic variability was assessed following the approach implemented in the MolKin software. Comparison was performed using the fixation index and the Reynolds genetic distance. The most likely number of different populations was estimated using the clustering procedure implemented in STRUCTURE. The molecular information suggests that management practices could have prevented random mating and produced inbreeding and heterogeneity across flocks. In this respect, Bionda and Bianca show substructuring and are more similar to British breeds than other continental European breeds. Bionda and Bianca fit into the European breeds provided with the highest number of alleles and expected heterozygosity. There is a clear distinction between the Piedmont breeds and the other populations. The Piedmont poultry differ from both commercial lines and other Italian breeds and retain a high level of genetic variability. As for other indigenous breeds, Bionda and Bianca could make an original contribution to the industry in the future. A collective planned approach to restoration is essential, because the flocks are managed with poor regulation. Enhancing connection between breeders with an efficient replacement interchange and mating plan is the right way of controlling inbreeding, preventing substructuring and increasing variability within the flocks.